Pengaruh Green Marketing dan Green Awareness terhadap Keputusan Pembelian Produk The Body Shop di Bali yang Dimediasi oleh Green Brand Image - Ni Putu Mirna Permatasari; Nuning Indah Pratiwi; Ni Nyoman Sri Wisudawati; Ni Kadek Winda Yanti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The cosmetics sector ranks among the foremost generators of plastic waste globally, encompassing Indonesia as well. In Bali, despite the enforcement of plastic reduction policies, inorganic waste continues to pose a formidable challenge. This research seeks to examine the impact of sustainable marketing and environmental consciousness on purchase intentions for The Body Shop products in Bali, positioning green brand perception as the mediating factor. Employing a quantitative approach, questionnaires were distributed to 170 participants selected via purposive sampling. The gathered data underwent analysis using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) via SmartPLS software. Findings reveal that decisions to acquire eco-friendly products are predominantly shaped by green brand image, surpassing the direct effects of sustainable marketing or environmental awareness. Furthermore, eco-brand perceptions effectively act as a bridging mechanism, connecting environmentally focused marketing strategies and green awareness to consumers' buying decisions. In conclusion, firms are urged to prioritize the cultivation of a robust, credible image of ecological responsibility, beyond mere promotional efforts, to drive authentic consumer purchasing actions.